Ad Hoc Networks Routing Protocols Efficiency With Respect To Connection Availability - Trajanov, Dimitar; Filiposka, Sonja; Cilku, Bekim; Grnarov, Aksenti (My University, 2004)
One of the most important issues in the main applications of mobile ad hoc networks (as rescue and military operations) is to know the availability of the system. We developed an analytical model in order to investigate the routing protocol efficiency using real measurable parameters that concern the performances of mobile ad hoc networks. We analyzed the routing protocol efficiency with respect to connection availability for rescue mission example application.
Keywords: Ad hoc Network, Connection Availability, Routing Protocols Efficiency, Availability Model